Mechanical reinforcement of bioceramics scaffolds via fracture energy dissipation induced by sliding action of MoS2 nanoplatelets. (November 2017) - Shuai, Cijun; Sun, Hang; Gao, Chengde; Feng, Pei; Guo, Wang; Yang, Youwen; Zhao, Mingchun; Yang, Sheng; Yuan, Fulai; Peng, Shuping
Abstract: The inherent brittleness of bioceramics restricts their applications in load bearing implant, although they possess good biocompatibility and bioactivity. In this study, molybdenum disulfide nanoplatelets (MSNPs) were used to reinforce bioceramics (Mg2 SiO4 /CaSiO3 ) scaffolds fabricated by selective laser sintering (SLS). The fracture mode of scaffolds was transformed from transgranular to mixed trans- and intergranular. It could be explained that MSNPs could slide easily due to their weak interlayer van der Waals interactions and provide elastic deformation due to their high elastic modulus. Such sliding action and elastic deformation synergistically induced crack bridging, crack deflection, pull-out and break of MSNPs. Those effects effectively increased the fracture energy dissipation and strain capacity as well as changed the fracture mode, contributing to high fracture toughness and compression strength. Additionally, the scaffolds with MSNPs not only formed a bioactive apatite layer in simulated body fluid, but also supported cell adhesion and proliferation. Graphical abstract: fx1 Highlights: The MSNPs reinforced bioceramics scaffolds were fabricated by SLS. Mechanical properties of composite scaffolds were improved by MSNPs. Reinforcing mechanisms were crack bridging, crack deflection and MSNPs pull-out. These mechanisms were attribute to the sliding and elastic deformation of MSNPs. The scaffolds with MSNPs exhibited favorable biocompatibility.